The Effects of Skin Aging Associated with the Use of BioCell Collagen: A Randomized, Double-blind, Placebo-controlled Clinical Trial (P06-122-19). (13th June 2019) - Schauss, Alexander; Schwartz, Stephen; Hammon, Kimberly; Hardy, Anna Gafner; Guttman, Norman; Fong, Michelle; Dahl, Amanda
Abstract: Objectives: The aim of the study intended to correlate the effects of the dietary supplement, BioCell Collagen, with any changes associated with skin aging, since dietary supplements claim cutaneous anti-aging properties for their products; however, research supporting these claims remains sparse. Methods: A 12-week, randomized, double-blind, placebo-controlled trial of 128 female subjects, aged 39–59 (50.57 ± 5.55) randomly assigned to treatment or placebo. Intervention: Twice daily oral administration of a supplement containing 500 mg of a naturally occurring matrix of collagen type-II peptides, hyaluronic acid, and chondroitin sulfate, derived from chicken sternal cartilage, or placebo. Primary outcome measures: trans-epidermal water loss, viscoelasticity, hydration, collagen content, chromophore (melanin) content and hemoglobin level, and photographic analysis. Expert visual grading for facial lines/wrinkles, crow's feet lines/wrinkles, skin texture/smoothness, and skin tone. Secondary outcomes: Tolerance and incidence of adverse events. Presence of erythema and/or dryness determined tolerance. Participant's perception of the product's value. Results: Dietary supplementation significantly reduced facial lines and wrinkles ( p  = 0.019), crow's feet lines/wrinkles ( p  = 0.05), increased skin elasticity ( p  = 0.05), cutaneous collagen content ( p  = 0.001), and improved indicators of youthful skin appearance and wrinkle width ( p  = 0.046), and decreased skin dryness and erythema, compared to placebo. There was no difference between supplement and placebo for skin surface water content or retention. Supplement was well tolerated with no reported adverse reactions. Conclusions: Dietary supplementation of this chicken sternal cartilage extract supports the accumulation of types-I/III collagen in skin to promote increased elasticity and reduced skin wrinkling in women 39 to 59 years of age. Funding Sources: BioCell Technology, LLC.